2009
DOI: 10.1016/j.jcrs.2008.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Salzmann-like nodular corneal degeneration after laser in situ keratomileusis imaged with anterior segment optical coherence tomography and high-frequency ultrasound biomicroscopy

Abstract: Examination of a 34-year-old patient 7 years after laser in situ keratomileusis (LASIK) showed Salzmann-like nodules in both eyes, causing irregular astigmatism and decreased visual acuity. Two new imaging modalities were used to demonstrate the characteristics of this complication. Anterior segment optical coherence tomography (OCT) (Visante) scans showed hyperreflective nodules that varied in thickness from 0.35 mm to 0.56 mm. High-frequency ultrasound biomicroscopy illustrated the destruction of Bowman laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…High-resolution anterior segment OCT confirmed that the nodules were subepithelial and not within the LASIK flap interface, as has been suggested by other authors 2. Histological analysis of the nodule was consistent with that previously described for Salzmann nodules4 5 and confirmed the findings from OCT 6.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…High-resolution anterior segment OCT confirmed that the nodules were subepithelial and not within the LASIK flap interface, as has been suggested by other authors 2. Histological analysis of the nodule was consistent with that previously described for Salzmann nodules4 5 and confirmed the findings from OCT 6.…”
Section: Discussionsupporting
confidence: 89%
“…Some authors have speculated that exacerbation of dry eye syndrome contributes to the formation of Salzmann nodules after LASIK 1 2. Although dry eyes cannot be ruled out as a solitary cause in our patient, the lack of significant clinical findings of dry eye syndrome (including punctate epithelial erosions), the unilaterality of the nodules and the distribution of the nodules overlying the epithelial ingrowth lead us to hypothesise that the presence of epithelial ingrowth itself was a contributing factor.…”
Section: Discussionmentioning
confidence: 59%
“…In most cases tissue samples are not available for histological examination and previous histological studies have been performed in advanced cases requiring penetrating or lamellar keratoplasty. The only study about the use of OCT imaging in Salzmann nodular degeneration has reported the morphology of a bilateral case, which developed after LASIK (13). However the low resolution of time domain anterior segment OCT prevented the authors from documenting the detailed morphology of Bowman’s layer underneath and epithelium overlying the Salzmann nodular degeneration lesions.…”
Section: Discussionmentioning
confidence: 99%
“…OCT can be used to assess the morphology of these nodules [40, 41]. Many of the established histopathologic findings can be seen using the Visante OCT in vivo [41].…”
Section: Role Of Oct In Excimer Laser Phototherapeutic Keratectomymentioning
confidence: 99%